Investigation into the influence of the interlayer temperature on machinability and microstructure of additively manufactured Ti-6Al-4V - Fuchs, Christina; Elitzer, Daniel; Höppel, Heinz Werner; Göken, Mathias; Zaeh, Michael F. (Production Engineering, 2023)
The capability of wire and arc additive manufacturing (WAAM) to produce large, near-net-shaped parts with inexpensive equipment has led to the process being considered as one of the options to significantly decrease the buy-to-fly ratio in aircraft manufacture. Even so, there are several challenges associated with the process: achieving mechanical properties and microstructure similar to wrought material, as well as the low surface quality of the parts. The low surface quality is usually improved by milling. As with the microstructure, here too the question arises as to whether the process is comparable to milling wrought material. A significant factor influencing the microstructure according to literature is the interlayer temperature during the WAAM process. Therefore, the objective of this research was to study the influence of the interlayer temperature on the machinability and the microstructure of wire and arc additively manufactured Ti-6Al-4V. Consequently, the machinability was first determined for Ti-Al6-V4-parts manufactured with three different interlayer temperatures. Then, the macro- and microstructures were analyzed and, finally, the mechanical properties were determined. Contrary to expectations based on the state of the art, the machinability was not influenced by the interlayer temperature. This aligns with the mechanical properties and the macro- and microstructures, which are only slightly affected by the interlayer temperature.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Interlayer temperature; Microstructure; Milling; WAAM